Instagram Social Media Marketing Communication Strategy in Increasing Sales at Malaika Wedding Planner (Approach Based on AIDA Model) - Ni Kadek Adela Amanda Putri; Luh Putu Citrawati; Ketut Arjaya (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to determine the Instagram social media marketing communication strategy at Malaika Wedding Planner. The research method used is descriptive qualitative with data collection techniques carried out through interviews, observations, and documentation. The informants interviewed consisted of business owners, social media marketing, and clients of Malaika Wedding Planner. The results of the study show that Malaika Wedding Planner uses a digital marketing communication strategy through Instagram that is based on the AIDA model. The application of the AIDA model marketing communication strategy is able to convert prospective brides and grooms into clients, thereby increasing sales at Malaika Wedding Planner. Thus, this study provides several important implications for other wedding organizer entrepreneurs. First, this study shows that Instagram social media can be an effective platform for increasing sales. Second, this study provides an example of the application of the AIDA model in a digital marketing communication strategy.